Standard specification for steel springs, helical, heat-treated. (American Society for Testing and Materials, 2007)
This specification covers hot-coiled, heat-treated helical compression springs with tapered, closed, squared and ground ends made of hot-wrought round steel bars 3/8 in. (9.5 mm) and larger in diameter.